Maternal Low-Protein Diet Impairs Prostate Growth in Young Rat Offspring and Induces Prostate Carcinogenesis With Aging - Santos, Sergio A A [UNESP]; Camargo, Ana C. [UNESP]; Constantino, Flávia B [UNESP]; Colombelli, Ketlin T. [UNESP]; Mani, Fernanda [UNESP]; Rinaldi, Jaqueline C. [UNESP]; Franco, Suelen [UNESP]; Portela, Luiz M F [UNESP]; Duran, Bruno O S [UNESP]; Scarano, Wellerson R. [UNESP]; Hinton, Barry T.; Felisbino, Sergio L. [UNESP]; et al. (Oxford University Press (OUP), 2019)
Carcinogenesis is frequently linked to genetic background, however, exposure to environmental risk factors has gained attention as the etiologic agent for several types of cancer, including prostate. The intrauterine microenvironment has been described as a preponderant factor for offspring health; and maternal exposure to insult has been linked to chronic disease in older offspring. Using a model of maternal exposure to low-protein diet (LPD; 6% protein), we demonstrated that impairment of offspring rat prostatic growth on postnatal day (PND) 21 was associated with prostate carcinogenesis in older offspring (PND 540). One explanation is that maternal LPD consumption exposed offspring to an estrogenic intrauterine microenvironment, which potentially sensitized prostate cells early during glandular morphogenesis, increasing cellular response to estrogen in older rats. The onset of accelerated prostatic growth, observed on PND 21, associated with an unbalanced estrogen/testosterone ratio and increased circulating IGF-1 in older offspring appears to contribute to the development of prostate carcinoma in groups on gestational low protein and gestational and lactational low protein diets (33 and 50%, respectively). Our study strongly indicated maternal exposure to LPD as a potential risk factor for induction of slow-growing prostate carcinogenesis in rat offspring later in life.
Keywords: Estrogen; IGF-1; Maternal low protein diet; Prostate cancer; Testosterone; Ventral prostate